Current Research Progress of Iron Deficiency in Heart Failure - Song, Jiahao; Fang, Zhimin; Sun, Jiaqi (Journal of Contemporary Medical Practice, 2025)
Iron is an essential element for human life activities, and it plays an important role in various life activities, such as oxygen transport and storage, electron transport in the oxidative respiratory chain, catalyzing the synthesis and decomposition of proteins, lipids or nucleic acids, iron-dependent cell death, etc. Iron deficiency is extremely common in patients with heart failure Iron deficiency (ID) is a common comorbidity in patients with heart failure, impairs exercise capacity, reduces the quality of life, increases hospitalisation rate and mortality risk regardless of anaemia. Intravenous iron therapy in patients with heart failure and iron deficiency has achieved considerable results, but how to effectively identify patients who are most likely to benefit from intravenous iron therapy remains controversial. This article reviews the mechanism of iron homeostasis in the body, and current diagnosis and treatment of iron deficiency in heart failure.